Challenges of Financial Management of the Higher EducationInstitutions in Georgia - Kasradze, Tea; Antia, Vakhtang; Gulua, Ekaterine (European Journal of Economics and Business Studies, 2022)
The funding of the higher education institutions and its efficient management affects the functioning of the whole system. The level of development of an education and science has an important role in the economic development of the country. Georgia has enough potential to achieve economic development by intellectual and educated human resources. Despite the reforms implemented in the recent years, there are still many shortcomings and challenges left in the education system that are hindering the creation of welleducated and competitive human resources. Without strengthening the education system, it is impossible to participate in a global competition. The increasing of financing of the education system over the years does not mean raising the quality of education. Developing the correct strategy and tactics of the reform and adequate and efficient distribution of financial resources is crucial. The aim of the paper is to study impact of the existing funding policy on higher education system in Georgia. The structure and dynamics of the funding of the higher education institutions, the nature and importance of the already funded projects are examined in the study. The issue of promotion of development of education through the reforms implemented in the education system is also discussed and analyzed in it. The study is based on the qualitative and quantitative analyses. The recommendations issued within the framework of the study will support stakeholders to overcome the current challenges and improve financial management policy of higher education institutions.